Pembentukan Self Control dalam Perspektif Nilai Multikultural - Lilik Sriyanti (Prodi PGMI IAIN Salatiga, 2012)
Self-control is a form of mental condition that affects the formation of a positive and productive behavior and determines the harmonious relationship to others. Recent deviant behavior, delinquency, promiscuity and the failure of a person’s life is strongly influenced by low self-control. The formation of self-control, at once, is influenced by cultural values that implied in parenting styles and learning outcomes of the behavior of those around him or her.Self-control is manifested in the form of empathy, tolerance and discipline that all motivated by the cultural establishment. Every culture has certain values considered valuable or valued. Javanese culture that values harmony with the environment, more appreciative to the collectivity than the personal self-interest, will form a better self-control. Similarly, the Javanese self-image as a cool, sincere in acceptance, patient and courteous person would lead one to try to control him or herself.Meanwhile, the Batak and Madurese society living in mountainous and rural areas with severe natural conditions requires a high spirit in order to conquer nature. Only tough, persistent and daring aggressive people can survive and succeed in life. Behaviors that are too impatient, calm and shy viewed as a personality in the weak tender, which cannot be used to subdue the ferocity of nature. This cultural background is the initial of why Batak and Madura people raise as more spontaneous, expressive, courageous and aggressive tended.